The Essential Factors for Overcoming Behavioral Problems with Positive Behavior Support Approach in Inclusive Schools - Aisyati, Wardah Wuri; Firdaus, Anastasia Syahidah; Zain, Zuhra Fadlulla; Hendriani, Wiwin (Universitas Islam Indonesia, 2025)
Behavioral problems among students have been observed to be a significant challenge that is prevalent in inclusive schools. An effective approach for addressing this issue includes the implementation of Positive Behavior Support (PBS). Therefore, this study aims to thoroughly explore important aspects of PBS and provide recommendations for the optimal implementation of the support program in inclusive schools using a Systematic Literature Review (SLR). In order to achieve the stated objective, the investigation adhered to the Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) guidelines to review relevant articles. The article search focusedon publications from the last 5-10 years (2014-2024). Accordingly, inclusion and exclusion criteria were established with a sole focus on studies related to the implementation or implications of PBS, Positive Behavioral Interventions and Supports (PBIS), or School-Wide Positive Behavioral Interventions and Supports (SWPBIS). Articles were sourced from the Scopus electronic database, and out of the 415 publications obtained related to the subject matter, 16 were observed to completely meet the inclusion criteria. The reviewed studies were observed to have predominantly adopted quantitative, qualitative, and mixed methods. The obtained results showed that the important aspects of implementing effective PBS in inclusive schools consisted of school readiness (teachers and staff), inclusiveness of parents, contributions of professionals, engagement of the surrounding community, effective communication and cooperation among stakeholders, comprehensive planning to program evaluation, and availability of adequate school facilities. Moreover, staff and teacher training is also an important prerequisite for schools intending to successfully implement PBS intervention programs.